Medicines with one seller and many buyers: strategies to increase the power of the payer. (20th May 2020) - Rintoul, Andrew; Colbert, Allison; Garner, Sarah; Kotwani, Anita; Vogler, Sabine; Bouvy, Jacoline; Hill, Andrew
Abstract : Andrew Rintoul and colleagues argue that collaboration and transparency increase the market power of buyers who face a monopoly